Modelling the dispersion of infectious salmon anemia virus from Atlantic salmon farms in the Quoddy Region of New Brunswick, Canada and Maine, USA - Fuhong Ding; Nellie Gagné; Delphine Ditlecadet; Brady K. Quinn; Marc Trudel (FACETS, 2024)
Pathogen dispersal from infected aquaculture sites into the surrounding ocean poses risks of infection to wild and farmed species, but is difficult to predict. This study aimed to build a framework using an ocean circulation and a particle tracking model in conjunction with a dynamic infection model and a virus inactivation model to simulate the dispersal of the infectious salmon anemia virus (ISAV) from Atlantic salmon farms. Simulated particles were released from hypothetically infected farms and advected by modelled currents. Inactivation of viral cohorts by ambient ultraviolet radiation and natural microbial communities was simulated during advection. Simulations showed that ISAV concentration varied spatiotemporally with the progression of the outbreak, current speed and direction, tidal elevation amplitude, and environmental decay. Connectivity among aquaculture sites varied in relation to seaway distances, though simulations showed that connectivity can also be asymmetrical between farm sites. Sensitivity analyses showed that the dispersal of ISAV was moderately sensitive to uncertainty associated with the viral decay model, highlighting the importance of obtaining accurate estimates of inactivation rates of ISAV. This framework provides an approach to simulate waterborne viral transmission that considers the biology and epidemic features of significance for pathogens and the dynamic conditions of the ocean.